Combination of the Simple Additive (SAW) Approach and Mixture Design to Determine Optimum Cocoa Combination of the Hot Chocolate Beverage - Dogan, Mahmut; Aktar, Tugba; Toker, Omer Said; Tatlisu, Nevruz Berna (TAYLOR & FRANCIS INC, 2015)
Physicochemical (pH, brix, and color), sensory (color, taste, odor, mouthfeeling, consistency, bitter flavor, and general acceptability), and rheological properties of the hot chocolate beverages including different cocoa combinations were investigated in the present study. Cocoa type significantly affected all of the properties. Simple additive weighting approach was applied to obtain one score from seven different sensory parameters and simple additive weighting score was used in mixture design to determine optimum cocoa type or cocoa combination. Ostwald de Waele model described the flow behavior of the hot chocolate beverage samples with R-2 values ranged between 0.818 and 0.999. The consistency coefficient (K) and apparent viscosity at shear rate 50 s(-1) (eta(50)) were significantly affected by cocoa type found in the formulation of the beverage. The mixture design approach was performed in order to determine variation of the responses (physicochemical, sensory, and rheological parameters) as a function of cocoa concentration. Simple additive weighting scores were satisfactorily described by established equation as a function of cocoa concentration to be used in the formulation of the hot chocolate beverage (R-2 = 0.8645).
Keywords: Cocoa; Sensory, Rheology; Mixture design; SAW; Hot chocolate; RHEOLOGICAL PROPERTIES; SENSORY PROPERTIES; BEHAVIOR; OPTIMIZATION; STARCHES; TERMS; Food Science & Technology